Natural Fermentation Quality and Bacterial Community of 12 Pennisetum sinese Varieties in Southern China - Zi, Xuejuan; Li, Mao; Yu, Daogeng; Tang, Jun; Zhou, Hanlin; Chen, Yeyuan (Frontiers in Microbiology, 2021)
This study investigated the fermentation quality of 12 varieties of Pennisetum sinese grown in different regions of Southern China. Following the production of silage from the natural fermentation of P. sinese, the interplay between the chemical composition, fermentation characteristics, environmental factors and microbiome was examined to understand the influence of these factors on the fermentation quality of silage. The silage quality produced by most of the P. sinese was low; the pH value of the silage was high (4.26-4.86), whilst the lactic acid content was low (10.7–24.1 g/kg DM), with V-scores between 57.9 and 78.3. The bacterial alpha diversities of the 12 P. sinese silages were distinct. There was a predominance of undesirable bacteria (Pseudomonas, Massilia and Raoultella), which likely caused the poor fermentation quality. The chemical composition and fermentation characteristics of the silage were closely correlated with the composition of the bacterial community. Furthermore, environmental factors (precipitation, temperature, humidity, location) were found to significantly influence the microbiome of the silage. The results confirmed that silage produced from the natural fermentation of 12 different P. sinese varieties had significant variation in their bacterial communities. The difference in environmental factors, due to the P. sinese being grown in various locations across south china, greatly affected the bacterial community found in the silage and thus the fermentation quality. The specific cultivar used for the silage and the environment in which the cultivar is grown must therefore be considered before the initiation of production of silage in order to ensure a higher quality product.